Expression of the Classical and Nonclassical HLA Molecules in Breast Cancer - Gisela Bevilacqua Rolfsen Ferreira da Silva; Tarsia Giabardo Alves Silva; Roberta Aparecida Duarte; Nicolino Lia Neto; Hélio Humberto Angotti Carrara; Eduardo Antônio Donadi; Maria Alice Guimarães Gonçalves; Edson Garcia Soares; Christiane Pienna Soares (International Journal of Breast Cancer, 2013)
Considering that downregulation of HLA expression could represent a potential mechanism for breast carcinogenesis and metastasis, the aim of the present study was to use immunohistochemical methods to analyze the expression of HLA-Ia, HLA-DR, HLA-DQ, HLA-E, and HLA-G in invasive ductal carcinoma (IDC) of the breast and to relate this HLA profile to anatomopathological parameters. Fifty-two IDC from breast biopsies were stratified according to histological differentiation (well, moderately, and poorly differentiated) and to the presence of metastases in axillary lymph nodes. The expression of HLA molecules was assessed by immunohistochemistry, using a computer-assisted system. Overall, 31 (59.6%) out of the 52 IDC breast biopsies exhibited high expression of HLA-G, but only 14 (26.9%) showed high expression of HLA-E. A large number (41, 78.8%) of the biopsies showed low expression of HLA-Ia, while 45 (86.5%) showed high expression of HLA-DQ and 36 (69.2%) underexpressed HLA-DR. Moreover, 24 (41.2%) of 52 biopsies had both low HLA-Ia expression and high HLA-G expression, while 11 (21.2%) had low HLA-Ia expression and high HLA-E expression. These results suggest that, by different mechanisms, the downregulation of HLA-Ia, HLA-E, and HLA-DR and the upregulation of HLA-G and HLA-DQ are associated with immune response evasion and breast cancer aggressiveness.